Distribution of Giardia duodenalis (Assemblages A and B) and Cryptosporidium parvum amongst migrant workers in Peninsular Malaysia - Sahimin, Norhidayu; Douadi, Benacer; Lim, Yvonne Ai Lian; Behnke, Jerzy Marian; Mohd Zain, Siti Nursheena (Elsevier, 2018)
The influx of low skilled workers from socioeconomically deprived neighbouring countries to Malaysia has raised concerns about the transmission of communicable gastrointestinal diseases such as giardiasis and cryptosporidiosis to the local population. Therefore, a cross sectional study was conducted to investigate the prevalence of both diseases and the genetic diversity of these pathogens in the migrant population. Microscopic examination of faecal samples from 388 migrant workers involved in five working sectors were screened and 10.8% (n = 42) were found to be positive with Giardia spp. and 3.1% (n = 12) with Cryptosporidium spp. infections. PCR amplicons at the triosephosphate isomerase (tpi) gene were successfully obtained for Giardia duodenalis from 30 (30/388; 7.73%) samples with assemblages AII and B in 13 (13/30; 43.3%) and 17 (17/30; 56.7%) positive samples, respectively. Nine samples (9/388; 2.3%) were identified as Cryptosporidium parvum using PCR-RFLP analysis. Country of origin, duration of residence in Malaysia and working sectors significantly influenced G. duodenalis assemblage AII infections amongst the targeted population. Meanwhile, C. parvum infection was significantly associated with those working in the food service sector. Despite the low presence of pathogenic G. duodenalis and C. parvum in the study population, the results highlight the risk of anthroponotic foodborne and waterborne transmission and therefore call for implementation of control strategies through improvements in personal hygiene and sanitation standards.